Asymmetric ligand transformation reactions promoted by cyclometallated complexes - Cheow, Yuen Lin (2012)
Complex bis(u-chloro)-bis{(R)-1-(dimethylamino)ethyl] naphtyl-C2,N} palladium (II) was found to successfully undergo insertion reactions at the palladium-carbon with the diphenylarsinoprop-1-yne ligand at room temperature which leads to the formation of a new 7-membered metallacyce in the inserted product. This reaction was also carried out on the platinum (II) metal template containing the naphythylamine moiety. The monoarsine precursor complexes has shown to undergo a C-H bond activation followed by a C-C bond coupling at room temperature. This reaction can only be initiated with the presence of a platinum (II) metal. The chiral organopalladium template was used to promote asymmetric hydroarsination reaction between diphenylarsine and various functionalised alkenyl phosphines with hydroxy, methoxy, dimethylamino, ester and ketone as functional groups. The asymmetric Diels-Alder reaction promoted by chiral platinum (II) metal template between DMPP and phenyldi[(Z)]prop-1-enyl]phosphine oxide showed poor stereoselectivity with two isomers (1:1) being formed. The cycloaddition reaction between DMPP and phenyldi[(Z)]prop-1-enyl]phosphine sulphide similarly showed poor selectivity.